The relationship between vision status and its influencing factors among primary and secondary school students: The masking effect of physical activity level and the moderating effect of academic stress - Jiyan Xu; Yanjun Li; Siyuan Ma; Shimeng Dai; Weiwei Xu; Mengjiao Sang; Kaijie Feng (BMC Public Health)
Abstract Background The global youth myopia rate continues to rise, and the vision health of primary and secondary school students has become a global concern. This cross-sectional study aims to explore the vision status of primary and secondary school students in the Ningxia Hui Autonomous Region, China, and its internal relationship with influencing factors under regional characteristics. Methods A survey was conducted among 1,670 primary and secondary school students in the Ningxia Hui Autonomous Region of China using a snapshot method and random sampling techniques from September to October 2023. The survey instruments included vision examination, the International Physical Activity Questionnaire, the Lifestyle Behavior Scale, and the Student Academic Stress Questionnaire. The data was tested with descriptive statistics, difference test, correlation analyses, regression analyses, and so on using SPSS 25.0 and SPSSAU, and the target model was established and tested for the goodness-of-fit with AMOS 23.0. Results There was a significant negative correlation between vision status and lifestyle behaviors (r=-0.360, p < 0.01), physical activity level (r=-0.058, p < 0.05). The physical activity level played a significant masking effect between lifestyle behaviors and vision status (a*b = 0.002, c’=-0.044), and academic stress played a moderating role in the process of lifestyle behaviors affecting physical activity level and vision status. A moderated mediator model was constructed and fitted well (RMSEA = 0.028, CFI = 0.953, NFI = 0.934). Conclusions The prevalence rate of myopia among primary and secondary school students in Ningxia Hui Autonomous Region is lower than the national average, and its prevalence is related to lifestyle behaviors, physical activity level, and academic stress. The impact of lifestyle behaviors on vision status is controlled by physical activity level and academic stress. A strategy of coordinated education involving families, schools, and communities should be implemented. Parents should avoid having excessive expectations and additional academic burdens on their children and encourage them to actively participate in sports; schools should fully implement the ‘’Double Reduction’’ policy, making myopia prevention and control an important part of health education; communities should carry out publicity work for myopia prevention and control, raising adolescents’ awareness of eye health.